1969
DOI: 10.1152/ajplegacy.1969.216.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of free fatty acids across the primate placenta

Abstract: Transfer of free fatty acids across the primate placenta. Am. J. Physiol. 216(l) : 143-147. I969.-The transfer of linoleicand palmitic-lJ4C acids from mother to fetus and vice versa was studied in monkeys prepared with maternal and fetal arterial and venous catheters. Both fatty acids were rapidly transferred across the placenta. The mechanisms of transfer of fatty acids were investigated by measuring sequences of esterifications in plasma and other

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…18 Insulin resistant individuals have higher fasting plasma triglyceride levels and greater leucine turnover. 19,20 Amino acids are insulin secretagogues and an increased flux on amino acids could stimulate foetal hyperinsulinaemia. Triglycerides are energy rich and placental lipases can cleave triglyceride and transfer free fatty acids to the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…18 Insulin resistant individuals have higher fasting plasma triglyceride levels and greater leucine turnover. 19,20 Amino acids are insulin secretagogues and an increased flux on amino acids could stimulate foetal hyperinsulinaemia. Triglycerides are energy rich and placental lipases can cleave triglyceride and transfer free fatty acids to the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…Together with other de novo synthesized fatty acids, OA constitutes about 80% of the fatty acids that accumulate in the newborn's fat mass [21]. The fetus synthesizes abundant OA, but receives limited fatty acids across the placenta [22] and is inefficient in trapping free linoleic acid (LA, 18:2n-6) as shown at least in primates [23]. This contributes to a high fetal OA/LA ratio that stimulates fetal delta-6 desaturase (FADS2) to synthesize Mead acid from OA, at the expense of AA from LA.…”
Section: Discussionmentioning
confidence: 99%
“…The present notion is that placental FA uptake takes place by facilitated diffusion of maternal albumin-bound FFA and those released from VLDL-TO by placental lipoprotein lipase (IS, 16). Studies in monkeys showed that FFA are both transferred from mother to fetus and from fetus to mother (38). No experiments regarding placental perfusion have been performed with LCPUFA in maternal circulation and fat-free AFP in fetal circulation.…”
Section: Discussionmentioning
confidence: 99%